Makói Cigány Magazin, VTV
Airdates 1999.12-2000.08., minorities, Magyarcsanád, Roma Minority Councils' meeting, folk music and dance performance, Roma unemployment, pigeon breeding, dance music band, the Károly family, kindergarten teacher, ambition to study, musician families, father Imre Kozma, president of the Hungarian Maltese Charity, specialised hospital nurse, land program, Gipsy band violinist, adults in primary school, music teacher, assistance for small businesses, musician in Paris, flood damage, municipal legal aid, entertainment